PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS 1 SEKOLAH DASAR MENGGUNAKAN MEDIA RODA PUTAR BACA - Didin Asriyanti; Anna Mariyani; Husna Imro’athush Sholihah (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2026)
Reading ability is one of the important aspects of learning in elementary school. Reading is also a language skill that must be mastered at the beginning of education, namely the elementary school level. This study aims to improve students' initial reading ability through the reading wheel media. This study is based on the low initial reading ability of grade I students at SDN 1 Tamanrejo. The research subjects were 24 students. This study used a classroom action research (CAR) approach, developed by Kemmis and Mc Taggart. Which consists of 4 stages: planning, implementation, observation, and reflection. Data collection techniques include documentation, interviews, observations, and tests. Data validity was tested by triangulation of sources and methods. The achievement indicator in the study is said to be successful if the student's ability score has reached 80%, then the study must be stopped. The results of the study show that the use of the reading wheel media successfully improves teacher skills, student activities, and students' initial reading abilities. This is evidenced by the acquisition of cognitive results in cycle I, as many as 15 students with a percentage of 62.5% were able to complete the KKTP, while in cycle II it increased by 24 students with a percentage of 100% were able to complete the KKTP. Student activity in cycle I obtained an average score of 18 with a good category and in cycle II there was an increase again with an average score of 21 including the very good category. Meanwhile, it can be seen that teacher skills in cycle I obtained a score of 17 with a good category, and in cycle II there was an increase again with a score of 19 in the very good category. Thus, the use of the rotating reading wheel media able to improve initial reading skills in Indonesian language lessons. ABSTRAK Kemampuan membaca merupakan salah satu aspek penting dalam pembelajaran di sekolah dasar. Membaca juga merupakan keterampilan berbahasa yang wajib dikuasai pada awal menempuh pendidikan yaitu jenjang SD. Penelitian ini bertujuan untuk meningkatkan hasil kemampuan membaca permulaan siswa melalui media roda putar baca. Penelitian ini didasari karena rendahnya kemampuan membaca permulaan siswa kelas I SDN 1 Tamanrejo. Subjek penelitian berjumlah 24 siswa. Penelitian ini menggunakan pendekatan penelitian tindakan kelas (PTK), yang dikembang oleh kemmis dan Mc Taggart yang terdiri dari 4 tahapan yaitu, perencanaan, pelaksanaan, pengamatan, dan refleksi. Teknik pengumpulan data meliputi dokumentasi, wawancara, observasi, dan tes. Validitas data diuji dengan triangulasi sumber dan metode. Indikator ketercapaian pada penelitian dikatakan berhasil jika nilai te kemampuan siswa sudah mencapai 80% maka penelitian harus di hentikan. Hasil penelitian menunjukan penggunaan media roda putar baca berhasil meningkatkan keterampilan guru, aktivitas siswa, serta kemampuan membaca permulaan siswa. Hal tersebut dibuktikan pada perolehan hasil kognitif pada siklus I sebanyak 15 siswa dengan persentase 62,5% mampu tuntas KKTP, sedangkan pada siklus II meningkat sebanyak 24 siswa dengan persentase 100% mampu tuntas KKTP. Aktivitas siswa pada siklus I didapat skor rata-rata 18 dengan kategori baik dan pada siklus II terjadi peningkatan lagi dengan skor rata-rata 21 termasuk kategori sangat baik. Sedangkan terlihat keterampilan guru pada siklus I mendapatkan skor 17 dengan kategori kategori baik, serta pada siklus II terjadi peningkatan lagi dengan skor 19 pada kategori sangat baik. Dengan demikian penggunaan media roda putar baca  mampu meningkatkan kemampuan membaca permulaan pada pelajaran bahasa Indonesia.